Halal certification mark, brand quality, and awareness: do they influence buying decisions of Nigerian consumers? - Jaiyeoba, Haruna Babatunde; Abdullah, Moha Asri; Abdul Razak, Dzuljastri (Emerald Publishing, 2020)
Purpose – This paper aims to ascertain whether halal certification mark, halal brand quality and halal awareness influence Nigerian consumers when making buying decisions. Design/methodology/approach – The researchers reflect on the newly collected data to shed light on the above issues from the perspective of Nigerian consumers. To this end, a questionnaire was developed and used to collect data from 282 respondents. The data collected were analyzed using both descriptive and inferential statistics. Findings – This study found that halal certification mark and halal brand quality are the most influential factors that contributed to the consumers’ buying decisions in Nigeria. Originality/value – Based on the findings of this study, the researchers have argued that more efforts are needed in the area of halal awareness in Nigeria. Similarly, the study argues that halal brand quality should always be held at the esteemed position. Based on the study’s findings, the authors have been able to fill the literature gap, particularly in the context of the Nigerian halal industry.